2005
DOI: 10.1080/09578810500367649
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Decentralisation in Developing Countries Pro-poor?

Abstract: Decentralisation has been advocated by donors and development agencies as an instrument to ensure broader participation of citizens as well as to improve local governance leading to poverty reduction from the bottom up. On the basis of a comprehensive review of nine case studies documented in the literature, this study questions this assumption. According to our findings, a clear link between decentralisation and a reduction in poverty cannot be established. Two important policy lessons emerge from this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 17 publications
2
43
0
2
Order By: Relevance
“…2 These three indicators in the earlier, more extended version of their research are similar though not identical to those outlined in the analytical framework for their later journal article (Jütting et al, 2005). 3 Crook is one exception, maintaining a more non-committal stance.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…2 These three indicators in the earlier, more extended version of their research are similar though not identical to those outlined in the analytical framework for their later journal article (Jütting et al, 2005). 3 Crook is one exception, maintaining a more non-committal stance.…”
Section: Resultsmentioning
confidence: 80%
“…It is only in this current decade that decentralization research has specifically focused on linkages with poverty reduction, with a number of studies published since the turn of the century (Bossuyt & Gould, 2000;Crook & Sverrisson, 2001;Von Braun & Grote, 2002;Crook, 2003;Vedeld, 2003;Jütting et al, 2004Jütting et al, , 2005. The findings of these studies are generally negative, concluding that decentralization has not had a significant impact on poverty levels.…”
Section: Decentralization and Poverty Reduction: A Reviewmentioning
confidence: 89%
“…complex responsibility of aquatic resource governance without the required professional support staff. AsJütting et al (2005) have suggested, these conditions are characteristic of decentralisation by default as opposed to one by design. The genesis, content and implications of the LGA 2004 for the AF sub-sector (although outside the ambit of this paper) could throw light on the nature of such drawbacks.…”
mentioning
confidence: 93%
“…Hence, the setting of centrally designed pro-poor policies on health or water backed by sectoral funds is a typical example of policy incoherence in terms of decentralization, but these policies can still be successful and appropriate, even when the benefits that stem from bringing governments closer to the people are not fully exploited (Jütting et al 2005). The challenge is how these policies can coexist with local participation and autonomy (Francis and James 2003).…”
Section: Introductionmentioning
confidence: 98%